Penerapan Lkpd Berbasis Problem Based Learning Terhadap Kemampuan Berfikir Kritis Siswa Kelas X Pada Materi Energi Terbarukan - Riadah, Riadah; Haryadi, Rudi; Guntara, Yudi (Jurnal Ilmiah Wahana Pendidikan, 2024)
One of the problems often faced in the field of education today is how to One of the problems often faced in the field of education today is how to improve the level of education. One important strategy that teachers must use in the teaching process is to ensure that students understand the material. This research uses a postpositivist research paradigm and quantitative approach, and uses a Quasi Experimental design with a nonequivalent control group design model. With experimental and control classes consisting of 56 students. The instruments used are interview sheets, test questions, validation and documentation. This research procedure is an adaptation of the ADDIE development model, the data analysis used is the normality test, homogeneity test and hypothesis test and N-Gain. The research results show that there is an influence of using Problem Based Learning (PBL) based LKPD as shown by the results of the T-Test analysis with sig. 0.000 > 0.05 and from the N-Gain results for the experimental class it was obtained that a value of 0.9369 was categorized as high compared to the control class with an N-Gain of 0.1781 which was categorized as low.